Analisis Keterampilan Berpikir Kritis dan Komunikasi Siswa pada Mata Pelajaran Biologi - Annisa Aulia Rosa Putri; Rahmawati Darussyamsu (FONDATIA, 2022)
Critical thinking and communication skills are skills that must be possessed by students. Critical thinking and communication skills of students are very important to measure, so that teachers can later apply appropriate learning strategies for students. The purpose of the study was to determine the critical thinking and communication skills of class XI students at SMA Negeri 2 Payakumbuh. This type of research is descriptive research. The sample in this study was 74 students of class XI MIPA SMA Negeri 2 Payakumbuh which consisted of eight classes. The sampling technique was simple random sampling. The instrument used is a questieon in the form of a vallid essay. Data analysis technique using Microsoft Excel. Based on the research, it is known that the criticical thinking skills of class XI students are still in low qualifications with an average of 56,09% and communication skills are in good qualifications with an average of 66,65%. These result are expected to provide information about critical thinking and communication skills so that teacher can apply appropriate learning strategies and models in developing students’ critical thinking and communication skills.